Czy w Gnieźnie wszyscy jeździli na łyżwach? Łyżwy z osady Targowisko w Gnieźnie – przyczynek do sposobów ich użytkowania w okresie średniowiecza - Waszczuk, Kamilla; Żychliński, Daniel; Prawniczak, Robert; Pachulski, Piotr (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2014)
Did Everybody in Gniezno Ice-Skate? Ice Skates from the Settlement Targowisko in Gniezno – on the Means of Their Use in the Middle Ages and Not Only When writing the present article, the question was posed how common the use of ice skates had been in the period of the Middle Ages, confirmed in the literature on the subject by numerous references and information. It has been assumed that the issue is very complex. On the one hand, ice-skating was treated cursorily – any object made of bone whose shape resembled a “boat” must have been an ice-skate – on the other hand, the common use of skates found no confirmation in interdisciplinary studies. Meanwhile, our micro- and macroscopic analyses of the finds originating from the settlement in Gniezno called Targowisko, supported in full the conjecture that, in very wet places, surrounded by water, “ice-skating”, both as a means of transportation and as a form of recreation (!) was a part of everyday life. Moreover, a definite scheme of research has been developed which can be applied to all artefacts designated as ice skates; in all periods of history. Simultaneously, during our research, there arose many new questions which shall be answered, we hope, as a result of further analyses and related considerations. They are very intriguing questions as they concern man.